2008
DOI: 10.4314/ajtcam.v4i4.31241
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, Wound Healing And Antioxidant Activities Of <i>Anthocephalus cadamba</i>

Abstract: Anthocephalus cadamba (Roxb.) Miq. Syn A. chinensis (Lamk) A. Rich (Rubiaceae) is ethnomedicinally widely used in the form of paste by tribe in western Ghats for treating skin diseases. In this context, antimicrobial potential of A. cadamba against a wide range of microorganisms was studied. To validate the ethnotherapeutic claims of the plant in skin diseases, wound healing activity was studied, besides antioxidant activity to understand the mechanism of wound healing. The alchoholic and aqueous extract of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…The bark extract has also been reported to be traditionally used as a hypoglycemic agent in Bangladesh (Ghani, 1998). While previous bioactivity studies on this plant revealed its analgesic, anti-infl ammatory, antimicrobial, anti-oxidant, antimalarial, antihepatotoxic activities, and antidiarrheal and wound-healing properties (Umachigi et al, 2007;Alam et al, 2008a,b), the phytochemical investigations resulted in the isolation of indole alkaloids, secoiridoids, triterpenes and saponins from this plant (Banerji, 1977;1978;Brown & Chapple, 1976;Kitagawa et al, 1996;Sahu et al, 1999;. In continuation of our phytochemical and pharmacological screening of Bangladeshi medicinal plants (Uddin et al, 2005(Uddin et al, , 2007aDatta et al, 2007;Nayeem et al, 2006;Saha et al, 2007;Alam et al, 2008a,b;Mazid et al, 2009;Ara et al, 2010;Miah et al, 2010), we report on the hypoglycemic and oxidative stress-reducing activities of the hydroethanolic extract of the flowering tops of A. cadamba in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bark extract has also been reported to be traditionally used as a hypoglycemic agent in Bangladesh (Ghani, 1998). While previous bioactivity studies on this plant revealed its analgesic, anti-infl ammatory, antimicrobial, anti-oxidant, antimalarial, antihepatotoxic activities, and antidiarrheal and wound-healing properties (Umachigi et al, 2007;Alam et al, 2008a,b), the phytochemical investigations resulted in the isolation of indole alkaloids, secoiridoids, triterpenes and saponins from this plant (Banerji, 1977;1978;Brown & Chapple, 1976;Kitagawa et al, 1996;Sahu et al, 1999;. In continuation of our phytochemical and pharmacological screening of Bangladeshi medicinal plants (Uddin et al, 2005(Uddin et al, , 2007aDatta et al, 2007;Nayeem et al, 2006;Saha et al, 2007;Alam et al, 2008a,b;Mazid et al, 2009;Ara et al, 2010;Miah et al, 2010), we report on the hypoglycemic and oxidative stress-reducing activities of the hydroethanolic extract of the flowering tops of A. cadamba in alloxan-induced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Bosser], Rubiaceae, is widely distributed throughout Bangladesh, Nepal, India, Myanmar, Sri Lanka, the Philippines, Indonesia, and Papua New Guinea (Banerji, 1977;1978;Sahu et al, 2000;Niranjan et al, 2000;GRIN Databases, 2010). Various parts of this plant have traditionally been used as an antidiuretic, in the treatment of fever, anemia and tumor, and for the improvement of semen quality (Umachigi et al, 2007;Dr. Duke's Phytochemical and Ethnobotanical Databases, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Duke's Phytochemical and Ethnobotanical Databases, 2007). While previous bioactivity studies on this plant revealed its antimicrobial, antioxidant and wound healing properties, antimalarial and antihepatotoxic activities (Umachigi et al, 2007), the phytochemical investigations resulted in the isolation of indole alkaloids, secoiridoids, triterpenes and saponins from this plant (Banerji, 1977;1978;Brown and Chapple, 1976;Kitagawa et al, 1996;Sahu et al, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…Bosser] of the family Rubiaceae is widely distributed throughout Bangladesh, Nepal, India, Myanmar, Sri Lanka, the Philippines, Indonesia, and Papua New Guinea (Banerji, 1977;1978;Sahu et al, 2000;GRIN Databases, 2007). Various parts of this plant have traditionally been used as an antidiuretic, in the treatment of fever, anaemia and tumour, and for the improvement of semen quality (Umachigi et al, 2007;Dr. Duke's Phytochemical and Ethnobotanical Databases, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The flowers are yellow in color (Handa et al, 1984a). Plant parts are used as a folk medicine in the treatment of fever and anemia, as antidiuretic, and for improvement of semen quality (Umachigi et al, 2007). The leaves are recommended as a gargle in cases of stomatitis (Slkar et al, 1996).…”
Section: Introductionmentioning
confidence: 99%